Morphometric Traits of Pote Goats Raised in Lowland Areas of Madura Island - Abdul Rohman; Tri Eko Susilorini; Kuswati Kuswati (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aimed to investigated the morphometric characteristics of Pote goats, a local Indonesian goat breed found in Bangkalan Regency, East Java Province. A total of 139 respondents participated in the study, providing 622 female and male Pote goats aged over three months as research materials. This study employed a descriptive research method, including surveys and interviews, to retrieve data using purposive sampling technique. Quantitative data, such as body weight and body size, were analyzed descriptively using the average and standard deviation. Qualitative data, including body color, facial shape/profile, horns, beard, papillae, rewos fur, and udder shape, were analyzed using phenotypic frequency. The findings of this study revealed that Pote goats in Bangkalan are a small type of local Indonesian goat based on the body weight of an adult female and a large type based on shoulder height. Body weight and body size were found to increase with age. Furthermore, the dominant qualitative characteristics of Pote goats in Bangkalan include white color on the body, convex facial profile, drooping and widened ears with relatively short size, straight right and left horns, mane ruff, no papillae, and jug-shaped udder.